Correlation between Mother's Behavior in Providing Early Complementary Feeding with the Incidence of Diarrhea - Nabila, Intan; Hananti, Freni Susilo; Abiddin, Andi Hayyun; Martiningsih, Wiwin; ACOB, Joel Rey U. (Health Gate, 2023)
Babies are golden periods because in this period the babies will experience very significant. One of the influences on a baby's growth and development is providing nutrients to the baby appropriately according to his age, one of which is a complementary food. The purpose study was to determine the relationship between maternal behavior in early breastfeeding and the incidence of diarrhea in infants, in addition to identify mothers' breastfeeding behavior, the type of complementary food given, and the incidence of diarrhea in early breastfeeding. The method used a Traditional Study Review design and used the keywords "mother's behavior," "early complementary food," and "Baby diarrhea." This review study used a population of Infants 0-6 months. Exposure to Maternal Behavior in Early Breastfeeding, Outcome Incidence of Diarrhea, and Design Study Journal Articles used a cross-sectional design approach, analytical correlation, and analytical observational survey. Results showed a relationship between mothers' behavior in early breastfeeding and the incidence of diarrhea in infants. Mothers giving complementary food for less than six months were caused by factors such as low maternal knowledge and skills, which refer to the mother's low level of education. Medical personnel must be more active in counseling parents, especially mothers who have babies, about early complementary food to minimize the incidence of diarrhea in babies.